Formulation of nutritious biscuits fortified with minced catfish and Ulva sp for malnourished children - Setiawati, Natalia Prodiana; Fateha, Fateha; Supriyanto, Agus; Mardiyana, Indri; Nurhayati, Nurhayati; Sihono, Sihono; Suryaningrum, Th. Dwi (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2025)
Stunting is a critical problem that deserves attention and has become a global problem. The approach to reducing stunting is to provide nutritious supplementary food in the form of biscuits for children, especially those who are malnourished. The purpose of this study is to formulate nutritious biscuits enriched with minced catfish as a source of amino acids and Ulva sp as a source of dietary fiber. Design expert software (DX13) ® was used to analyze sensory data gathered from a hedonic scale assessment with 25 trained panelists to determine the best formulation for the fortified biscuit product. Taste and texture were among the sensory qualities that were assessed. In addition, physical aspects such as hardness and color (L, a, and b) are analyzed to determine the quality of the biscuit formula. The best formulas based on sensory evaluation and physical analysis undergo further analysis of their nutritional composition, including proximate analysis and amino acid profile.The best quality products found are biscuits fortified with a formula consisting of 33% wheat flour, 14% chopped catfish, and 1% Ulva flour.The state of the art of this research is the development of functional biscuits fortified with a combination of animal protein (catfish) and dietary fiber as well as antioxidants form Ulva sp., using an RSM-based formulation optimization approach to produce a highly nutritious product that isacceptable to children.